Genetic analysis of the cardiac methylome at single nucleotide resolution in a model of human cardiovascular disease - Johnson, Michelle D; Mueller, Michael; Adamowicz-Brice, Martyna; Collins, Melissa J; Gellert, Pascal; Maratou, Klio; Srivastava, Prashant K; Rotival, Maxime; Butt, Shahena; Game, Laurence; Atanur, Santosh S; Silver, Nicholas; et al. (PLoS genetics, 2014)
Epigenetic marks such as cytosine methylation are important determinants of cellular and whole-body phenotypes. However, the extent of, and reasons for inter-individual differences in cytosine methylation, and their association with phenotypic variation are poorly characterised. Here we present the first genome-wide study of cytosine methylation at single-nucleotide resolution in an animal model of human disease. We used whole-genome bisulfite sequencing in the spontaneously hypertensive rat (SHR), a model of cardiovascular disease, and the Brown Norway (BN) control strain, to define the genetic architecture of cytosine methylation in the mammalian heart and to test for association between methylation and pathophysiological phenotypes. Analysis of 10.6 million CpG dinucleotides identified 77,088 CpGs that were differentially methylated between the strains. In F1 hybrids we found 38,152 CpGs showing allele-specific methylation and 145 regions with parent-of-origin effects on methylation. Cis-linkage explained almost 60% of inter-strain variation in methylation at a subset of loci tested for linkage in a panel of recombinant inbred (RI) strains. Methylation analysis in isolated cardiomyocytes showed that in the majority of cases methylation differences in cardiomyocytes and non-cardiomyocytes were strain-dependent, confirming a strong genetic component for cytosine methylation. We observed preferential nucleotide usage associated with increased and decreased methylation that is remarkably conserved across species, suggesting a common mechanism for germline control of inter-individual variation in CpG methylation. In the RI strain panel, we found significant correlation of CpG methylation and levels of serum chromogranin B (CgB), a proposed biomarker of heart failure, which is evidence for a link between germline DNA sequence variation, CpG methylation differences and pathophysiological phenotypes in the SHR strain. Together, these results will stimulate further investigation of the molecular basis of locally regulated variation in CpG methylation and provide a starting point for understanding the relationship between the genetic control of CpG methylation and disease phenotypes.
Keywords: DNA Methylation; modely nemocí na zvířatech; Rats, Inbred BN; sekvence nukleotidů; Male; metylace DNA; Sequence Analysis, DNA; potkani inbrední SHR; sekvenční analýza DNA; Myocardium; potkani inbrední BN; mužské pohlaví; jednonukleotidový polymorfismus; krysa rodu Rattus; kultivované buňky; kardiovaskulární nemoci; genom; kardiomyocyty; Animals; lidé; Polymorphism, Single Nucleotide; Humans; zvířata; Rats; Disease Models, Animal; Myocytes, Cardiac; Rats, Inbred SHR; Cells, Cultured; Base Sequence; Cardiovascular Diseases; Genome; myokard